Challenges and Opportunities in Repurposing Natural Products for the Treatment of Neglected Trophical Diseases: A Review of Scaffold Optimization Strategies - Abubakar, Musa Yahaya; Mathew, Twan Sale; Shamsuddeen, Ruslan; Abdullahi, Saeed; Bilyamin, Ansar; Chinedu, Emmanuel Kinsley (Darul Yasin Al Sys, 2024)
Neglected Tropical Diseases (NTDs) are serious health issues that affect the entire world, especially in low-income tropical and subtropical areas, yet they do not get enough facilities. Natural items have great potential for treating NTD because of their varied chemical scaffolds. Nevertheless, there are a number of difficulties in optimizing these scaffolds for drug development. Attempts at synthesis and modification are complicated by the structural complexity of natural compounds. Economic and regulatory hurdles also obstruct advancement. Despite these difficulties, there are plenty of chances. Natural products are a significant source of structural variety that makes them ideal for drug discovery. developments in biotechnology and synthetic biology. Sustainable production is improved via biotechnology. Targeted optimization is made easier by advances in computer power and molecular understanding. Research collaborations can expedite the process of discovery and development. Finding efficient scaffolds can be done quickly by looking for NTD activity in already-existing natural product libraries. By tackling these issues scientifically and cooperatively, we can develop novel, practical, and affordable treatments for non-traumatic disabilities (NTDs), which will eventually improve the health of impacted communities.